Understanding Local Governance in the Circle of Interest: A Literature Review - Muhammad Wahyu Prasetyo Adi (CV. Era Digital Nusantara, 2025)
Abstract: Local public administration is a field that positively reflects organizational needs. As a result, public administration is required to provide concrete representation of its suitability to be called a public organization. Paradoxically, when local government public administration emphasizes representation, it has no substantive meaning. Purpose: This is the result of the interests of actors who have carved out administrative boundaries. Design/Methodology/Approach: This study uses a literature review that raises local issues conditioned in the form of specific subheadings with limitations. Maximizing data based on relevant research and sources forces this study to extract metadata from the data. To maximize metadata conditions, this study limits several relevant notes to support the main focus on public governance in the arena of interest. Findings: The results of the study show that pragmatic governance under pressure from capital owners has defeated senior policy experts, intellectual groups, and even political actors themselves. This existence is reflected in selective diction. This confirms the next finding, a shift from potential policies to administrative violations. The procurement of goods and services has become the most distributive consequence, ensuring that the basis for selective implementation is accommodated in concrete terms. Restoring the spirit of independence of supervisory institutions and involving external civil society-based institutions are areas that need to be considered in both the process and implementation. Originality/value: The conditioning of public governance does not ensure that it has been addressed by different actors with diverse focuses.